Bacterial Pathogen Profiles and Antibiotic Resistance in Pediatric Leukemia Patients: Insights for Optimizing Infection Management in Immunocompromised Children - Cristina Elena Singer; Alin Iulian Silviu Popescu; Renata Maria Văruț; Mihaela Popescu; Dira Loredana; Kristina Radivojevic; Petrescu Ileana Octavia (Antibiotics)
Background: This study investigates bacterial etiology and antibiotic resistance in pediatric leukemia patients to determine the impact of chronic pathology on treatment efficacy. Methods: Thirty cases of children aged 1–16 years (18 boys, 12 girls) were analyzed, identifying 13 pathogens, including 8 Gram-positive and 5 Gram-negative bacteria. Results: Among the patients, 11 girls presented with acute lymphoblastic leukemia (ALL) type B, while one boy and one girl had acute myeloid leukemia, and, as for boys, three had ALL type T and two had pre-B ALL. The most common pathogens were methicillin-resistant Staphylococcus aureus (MRSA, 11 patients), methicillin-sensitive Staphylococcus aureus (MSSA, 6 patients), Klebsiella spp., and Staphylococcus epidermidis. Due to the patients’ compromised health, most required intensive care and strong antibiotic regimens, including linezolid, vancomycin, and ertapenem, which showed limited resistance. Conclusions: These findings highlight the critical importance of understanding bacterial resistance patterns to guide effective treatments in vulnerable populations. Knowing specific resistance profiles can be lifesaving, allowing for tailored therapies that improve survival rates in children with leukemia facing serious bacterial infections. Focusing on the dual aspects of pediatric patients and multidrug-resistant bacterial infections, this study aims to highlight the importance of addressing these factors together to enhance therapeutic approaches in vulnerable populations.